20-Hydroxyecdysone-responsive microRNAs of insects. Issue 10 (2nd October 2020) - Jin, Xiaoli; Wu, Xiaoyan; Zhou, Lanting; He, Ting; Yin, Quan; Liu, Shiping
ABSTRACT: 20-Hydroxyecdysone (20-HE) plays essential roles in coordinating developmental transitions of insects through responsive protein-coding genes and microRNAs (miRNAs). The involvement of single miRNAs in the ecdysone-signalling pathways has been extensively explored, but the interplay between ecdysone and the majority of miRNAs still remains largely unknown. Here, by small RNA sequencing, we systematically investigated the genome-wide responses of miRNAs to 20-HE in the embryogenic cell lines of Bombyx mori and Drosophila melanogaster . Over 60 and 70 20-HE-responsive miRNAs were identified in the BmE cell line and S2 cell line, respectively. The response of miRNAs to ecdysone exhibited a time-dependent pattern, and the response intensity increased with extending exposure to 20-HE. The relationship between ecdysone and the miRNAs was further explored through knockdown of ecdysone-signalling pathway genes. Specifically, ecdysone regulated the cluster miR-275 and miR-305 through the coordination of BmEcR-B and downstream BmE75B, and the interaction between BmEcR and miR-275 cluster was strengthened by the feedback regulation of BmE75B . Ecdysone induced miR-275-3p and miR-305-5p through the ecdysone response effectors (EcREs) at the upstream of the pre-miR-275 cluster. Overall, the results might help us further understand the relationship between ecdysone signalling pathways and small RNAs in the development and metamorphosis of insects.